CATALYTIC COMBUSTION OF SOOT ON Ce-DOPED LANTHANUM COBALTITES - PECCHI,GINA (Sociedad Chilena de Química, 2014)
Substituted La1-xCe xCoO3 perovskite-type oxides (0.0≤x≤0.9), prepared by the self-combustion method, have been investigated as catalysts in soot combustion. The characterization results indicate modification in the specific surface area, crystal structure, oxygen mobility and reducibility of cobaltite upon cerium substitution. Cobaltite structure does not tolerate more than 50% substitution of La by Ce. For higher Ce substitution the perovskite structure is lost and mixed oxides are detected. Further destruction of the perovskite structure in a reductive process indicates a lower catalytic role of the perovskite structure in the catalytic combustion of soot regarding to the chemical composition of the La1-xCe xCoO3 system. After the reductive process, only a slight increase in the catalytic activity of the samples with low Ce content (x≤0.3) while a larger increased was detected for those with larger amount of Ce(x≥0.5). These results suggest that the activity of these materials for soot combustion is improved by two factors: i) the increasing of CeO2 content, closely related to higher material capacity for oxygen transfer from catalyst to carbonaceous surface and ii) the formation of larger CeO2 crystals in the higher-Ce-content samples after H2 reduction, responsible of the improvement of the oxygen exchange and number of contact points between catalyst and soot.